Effect of Physical Activity and Gender on Malnutrition Risk Among a Group of Elderly Jordanians - Al-Zeidaneen, S.A.; Al-Bayyari, N.S.; Ismail, Y. (Pakistan Journal of Nutrition, 2017)
Background and Objective: This study was designed to assess the prevalence of malnutrition and it’s associated risk factors among elderly Jordanians and to evaluate the effect of physical activity and gender on malnutrition risk. Materials and Methods: In this cross sectional study, sixty elderly individuals (>65 years) were screened for the risk of malnutrition based on gender and physical activity. Malnutrition risk scores were calculated using the nutrition screening initiative (NSI) DETERMINE checklist and the mini-nutritional assessment short-form (MNA-SF). Results: According to the NSI and MNA-SF, 48.7 and 18.3% of study participants were malnourished, respectively. The NSI checklist revealed significant differences (p